In silico design of a multi-epitope Chimera from Aedes aegypti salivary proteins OBP 22 and OBP 10: A promising candidate vaccine - Sathish Sankar (Journal of Vector Borne Diseases, 2022)
Background & objectives: The emergence and re-emergence of arboviruses such as dengue, Chikungunya and Zika viruses causing morbidity and mortality around the globe are of serious concern. A safe and effective vaccine is essential to control viral transmission. The salivary proteins of the mosquito that aid in blood probing, feeding and development are immunogenic. We aimed to report a multi-epitope candidate vaccine chimera from Aedes aegyptii mosquito salivary proteins OBP 22 and OBP 10 that could confer protection against all pathogens transmitted by the vector. Methods: Linear and conformation B-cell epitopes and MHC class-I and class-II binding T- cell epitopes were predicted using bioinformatic tools. Selected B- and T-cell epitopes were chosen for designing a multiepitope vaccine construct. The chimeric construct was analyzed for its immunogenicity, TAP and proteasomal cleavage, allergenicity, and structural validation for its suitability to be used as a candidate vaccine. Molecular docking was carried out to analyze the binding interactions with TLRs molecules. Results: A chimeric multiepitope vaccine was designed with the best-selected combination of immunogenic B-cell epitope, cytotoxic and helper T-cell and gamma interferon inducing epitopes with suitable adjuvant and linkers. The interacting residues between the candidate vaccine and the TLR molecules have been identified. Interpretation & conclusion: The proposed multiepitope candidate vaccine was designed from the mosquito salivary protein OBP 22 and OBP 10. The candidate vaccine was found promising for the protection against arboviruses. Further clinical validation is warranted to prove its efficacy, safety and immunogenicity for its potential use.